(untitled) (BALEAP Journal of Research and Practice, 2025)
This paper explores the extent to which Transnational Education (TNE) both deconstructs and reconstructs EAP thinking and practices. In our conference symposium, we used the acronym RANT to discuss our TNE challenges across four interrelated themes: Reconstructing Identity; Assessment; (K)Nowledge sharing and Transitions. Writing the paper gave us scope for reflection and space to consider the positive aspects of TNE as well as the cyclical nature of ranting. As a result, our RANT developed a more measured, reflective tone, which led to a revised version: Reflect, Assess, Negotiate, and Transform. The paper comprises 5 vignettes exploring challenges affecting EAP teacher identity, assessment, knowledge sharing, power relations, and equity within our various TNE and EMI contexts.